PENGEMBANGAN SISTEM KEAMANAN INFORMASI BERKELANJUTAN DENGAN TEKNOLOGI KRIPTOGRAFI - Prayoga, Estu (STMIK KAPUTAMA, 2024)
In the era of digitalization, ensuring the security of information has become a critical concern for organizations. This paper explores the development of sustainable information security systems by leveraging cryptography technology. The study begins with a comprehensive review of contemporary challenges in information security and recent advancements in cryptography. It then discusses the integration of cryptography into the design and implementation of information security systems to achieve sustainability goals. Furthermore, a case study is presented to illustrate the practical application of sustainable information security system development with cryptography. The findings emphasize the importance of incorporating cryptographic techniques in addressing security threats while promoting sustainable practices. This paper contributes to the understanding of how organizations can enhance their information security posture while embracing principles of sustainability.